„Zaszczute wilczęta”, „zagubione owce”, „robactwo” i „jad nienawiści” – zwierzęta w sowieckiej propagandzie walczącej z religią - Bugaj, Tomasz (Zoophilologica. Polish Journal of Animal Studies, 2020)
In the scientific study, the images of animals, which function in the texts, were examined. Propaganda created in the Soviet Union. They were targeted at a specific group social – people who share the view into the existence of God. Propaganda in its content referred to the Slavic folklore. Monsters, hyenas, jackals, rodents, hydras and insects serve the creators to introduce “aliens” or “enemies.” Based on the analysis of metaphors, comparisons, compounds phraseological and other means of expression are presented in a way that discredits how people are discredited, and so are the animals. Stereotypical perception of living beings, disdainful attitude towards them and prejudices had an impact on inducing certain attitudes and behaviours (anxiety, disgust, hatred) in the recipients, which in the end strengthened the process of stigmatization, discrediting and marginalisation. Soviet propaganda, using images of animals perceived as beings with much lower statutes. It has contributed to the social exclusion of religious groups and strengthened the power of stigma, that’s already been given to some living organisms.